Investigation on the effect of Mozart's Sonata K448 on relapse after fear memory extinction regarding control in female mice with dysbiosis (Research, Society and Development, 2024)
This study aimed to investigate the effect of Mozart's Sonata K448 on relapse after fear memory extinction in female mice with dysbiosis. A total of eight pregnant mice were used, and their female offspring were divided into two groups: G1 (Mozart, N = 8) and G2 (Control, N = 8). The mice were exposed to the corresponding music from 9:00 PM to 7:00 AM, from the intrauterine period until euthanasia. The methodology included a Habituation Test, Aversive Training, and Memory Extinction Test, with all procedures being recorded on video. The data obtained were analyzed using the Student's t-test for training and ANOVA for the tests, with a significance level set at p ≤ 0.05. The results showed no significant difference between the groups in the recall test (t(14) = 0.379; p = 0.710). The mean ± standard error of the mean for the Mozart group was 3.09% ± 0.88%, while for the Control group it was 2.69% ± 0.57%. It is concluded that exposure to Mozart's Sonata K448 did not have a significant impact on fear memory relapse in mice, contrasting with previous research suggesting benefits of music on memory.